Preliminary assessment of the conch fishery on the shelf and banks off the South Coast of Jamaica - Mahon, Robin (Caricom Fisheries Management Unit Belize CityBZ, 1992)
Recent rapid expansion in the fishery for conch on the South Coast and banks south of Jamaica particularly Pedro Bank, leads one to fear that this continued harvesting will lead to severe over exploitation. This could cause the fishery to collapse with considerable loss in revenue. Management options are suggested.